Facilitating Collaboration Through a Co-Teaching Field Experience - Mark S Montgomery; Adam Akerson (Networks: An Online Journal for Teacher Research, 2019)
This article describes an action research project in which two teacher educators implemented a co-teaching field experience with pre-service teacher candidates acting as co-teachers to facilitate collaboration among peers. The goal of the action research was to better meet the needs of pre-service teacher candidates and continually develop their ability to grow as reflective and collaborative future teaching educators. To increase collaboration, co-teaching models were implemented in an early field experience. Teaching activities and assignments provided opportunities for collaboration as co-teachers and as members of a teaching community. Data collection and observations indicate peer-to-peer co-teaching helped create a collaborative atmosphere for PTCs, while also revealing areas that need additional refinement in the field experience course.
Keywords: collaboration; co-teaching; field experience; pre-service teachers